Archaean Plate Tectonics in the North Atlantic Craton of West Greenland Revealed by Well-Exposed Horizontal Crustal Tectonics, Island Arcs and Tonalite-Trondhjemite-Granodiorite Complexes - Garde, Adam Andreas; Windley, Brian Frederick; Kokfelt, Thomas Find; Keulen, Nynke (Frontiers in Earth Science, 2020)
The 700 km-long North Atlantic Craton (NAC) in West Greenland is arguably the best exposed and most continuous section of Eo- to Neoarchaean crust on Earth. This allows a close and essential correlation between geochemical and isotopic data and primary, well-defined and well-studied geological relationships. The NAC is therefore an excellent and unsurpassed stage for the ongoing controversial discussion about uniformitarian versus non-uniformitarian crustal evolution in the Archaean. The latest research on the geochemistry, structural style, and Hf isotope geochemistry of tonalite-trondhjemite-granodiorite (TTG) complexes and their intercalated mafic to intermediate volcanic belts strongly supports previous conclusions that the NAC formed by modern-style plate tectonic processes with slab melting of wet basaltic oceanic crust in island arcs and active continental margins. New studies of the lateral tectonic convergence and collision between juvenile belts in the NAC corroborate this interpretation. Nevertheless, it has repeatedly been hypothesised that the Earth’s crust did not develop by modern-style, subhorizontal plate tectonics before 3.0 Ga, but by vertical processes such as crustal sinking and sagduction, and granitic diapirism with associated dome-and-keel structures. Many of these models are based on supposed inverted crustal density relations, with upper Archaean crust dominated by heavy mafic ridge-lavas and island arcs, and lower Archaean crust mostly consisting of felsic, supposedly buoyant TTGs. Some of them stem from older investigations of upper-crustal Archaean greenstone belts particularly in the Dharwar craton, the Slave and Superior provinces and the Barberton belt. These interpreted interactions between these upper and lower crustal rocks are based on the apparent down-dragged greenstone belts that wrap around diapiric granites. However, in the lower crustal section of the NAC, there is no evidence of any low-density granitic diapirs or heavy, downsagged or sagducted greenstone belts. Instead, the NAC contains well-exposed belts of upper crustal, arc-dominant greenstone belts imbricated and intercalated by well-defined thrusts with the protoliths of the now high-grade TTG gneisses, followed by crustal shortening mainly by folding. This shows us that the upper and lower Archaean crustal components did not interact by vertical diapirism, but by subhorizontal inter-thrusting and folding in an ambient, mainly convergent plate tectonic regime.